Using McClelland’s Theory of Need to Determine the Relationship between the Motivational Factor and Social Entrepreneurship Activity among People with Disabilities - Nurul Fatihah Ramdan; Syukrina Alini Mat Ali; Mohd Ali Bahari Abdul Kadir (Information Management and Business Review, 2023)
Social entrepreneurship (SE) refers to an activity where a social element is used to create business opportunities. It describes the efforts of certain non-profit organizations or government agencies to improve the social and economic conditions of impoverished communities. This paper proposes a conceptual model to examine the relationship between motivational factors and the engagement of people with disabilities (PWD) in SE activities. Using McClelland's need theory for measuring motivation, examines achievement, affiliation, and power needs. When these needs go unfulfilled, motivation declines, leading to decreased performance and turnover within the organization. This theory holds significant influence in entrepreneurship and has been widely adopted in various research studies. Conducting a quantitative survey among actively engaged PWDs in SE activities under the Social Welfare Department institution will help identify the motivational factors driving PWDs to prioritize social entrepreneurship over other employment options. Recognizing this connection enables government agencies and stakeholders to potentially reshape and create better-suited programs for PWD and guide them toward a renewed path of empowerment.